Meta-Analysis the Effect of a Potassium Nitrate Desensitizing Agent and Casein Phosphopeptide Amorphous Calcium Phosphate on Tooth Sensitivity after Office Bleaching Treatment - Safitri, Diyanti; Pamungkasari, Eti Poncorini; Murti, Bhisma (Indonesian Journal of Medicine, 2023)
Background: Office bleaching is a treatment used to treat tooth discoloration, but it often results in tooth sensitivity. The desensitizing agent potassium nitrate and casein phosphopeptide amorphous calcium phosphate (CPP-ACP) can reduce tooth sensitivity because they work to inhibit nerve transmission, thereby preventing the sensation of pain. This study aimed to investigate the effect of potassium nitrate desensitization agents and CPP-ACP on tooth sensitivity after bleaching treatment.Subjects and Method: This was a meta-analysis with the following PICO format. Population= Patients who have undergone office bleaching treatment. Intervention= desensitizing agents potas-sium nitrate and CPP-ACP. Comparison: without desensitizing agent. Outcome: tooth sensitivity. Keywords used "Office bleaching" AND "Tooth sensitivity" OR "Dentine hypersensitivity" AND "Potassium nitrate" AND Casein Phosphopeptide Amorphous Calcium Phosphate" OR "CPP-ACP" AND "Randomized Controlled Trial" OR “RCT”. Studies published at PubMed, Springerlink, Cochrane Database, Hindawi, Elsevier, Google Scholar and Wiley Online Library databases, from 2013 to 2023. The selected articles were critically reviewed using the PRISMA checklist and analyzed using the Review Manager 5.4.1. The effect size used is the Standardized Mean Difference (SMD).Results: A total of 13 RCTs from Brazil, Spain, India, Pakistan, Turkey, Jordan, Iran, and the United States was selected for meta-analysis. Meta-analysis of 7 articles shows that the use of potassium nitrate desensitization agents can reduce tooth sensitivity by 0.20 units lower than without the use of desensitization agents (SMD= - 0.20; 95% CI= -0.37 to -0.03; p=0.020). Meanwhile, 7 articles show that the use of CPP-ACP desensitization agents can reduce tooth sensitivity by 0.46 units lower than without the use of desensitization agents (SMD= -0.46; 95% CI= -0.67 to - 0.24; p<0.001).Conclusion: The use of potassium nitrate desensitization agents and CPP-ACP reduces tooth sensitivity compared to without the use of potassium nitrate desensitization agents and CPP-ACP and is statistically significant. Keywords: desensitizing agent, potassium nitrat, casein phosphopeptide amorphous calcium phosphate, tooth sensitivity, office bleaching